Pengembangan Media Pembelajaran Berbantuan Note Taking untuk Meningkatkan Keterampilan dalam Menulis Cerpen pada Siswa Kelas XI SMK Musda Perbaungan - Parwati, Juliya; Rita, Rita; Safina, Nila (Medan Resource Center, 2024)
This study aimed to enhance short story writing skills among class XI students at SMK Musda Perbaungan. The population comprised 481 students, with a sample size of 32 students from class XI TKJ 1. Data collection involved observation, interviews, and questionnaires. Research followed the Borg and Gall's 10-stage research and development (R&D) model. Results indicated that note-taking assisted learning media could improve short story writing skills. Material experts rated the media as